O mal estar covidiano no Brasil: um ensaio psicanalítico a partir da pandemia. - Assunção, Katarina Vieira (2024)
The Covid-19 virus was a device of fear for all humanity, especially in the pre-vaccine period, which acted as a total deprivation event. However, the condition and experience of helplessness were only experienced by countries whose management of the health crisis was flawed, as occurred in Brazil. Through the propagation of fake news, that was former by president Jair Messias Bolsonaro promoted a split in reality, inscribing the formation of neurotic group states and psychotic group states. This mass phenomenon led to a polarization in social relations, which resulted in the unveiling of issues that make up two pillars of civilization, which are politics and religion. Until the Covid-19 pandemic, our culture's aesthetic mark was the discursive and symbolic silencing of antagonism, especially in relation to issues that touched on the aforementioned pillars, which became the protagonists of the pandemic experience in Brazil. The phenomena that were being presented at the clinic served as triggers for the present research, whose main objective was to psychoanalytically study the malaise in Brazil, following the pandemic. To construct an analysis of this problem, I made use of the Maturity Theory, proposed by Winnicott, as well as his notion of democracy and the concept of Civilization and Discontent, proposed by Freud. Furthermore, I borrowed what some contemporary authors wrote about the pandemic phenomenon in the light of psychoanalysis, such as Birman, Bollas and Quinet. In view of the analysis constructed in this dissertation, which proposed an academic essay in psychoanalysis, we are experiencing a transformation in the ways of living and feeling unwell today, which is why I suggest the term Covidian Malaise.